Faktor-Faktor Yang Mempengaruhi Pencegahan Fraud Dalam Pengelolaan Keuangan Desa - Anandita Zulia Putri; Frida Dwi Prasiwi (Akmenika: Jurnal Akuntansi dan Manajemen, 2021)
This study aims to determine the factors that affect fraud prevention in village financial management. The influencing factors are organizational culture, morality, apparatus competence, and internal control system. This research was conducted in 13 sub-districts in Jetis,S edayu and Bantul Districts. This sample uses purposive sampling technique. The criteria used are village officials who are involved in village financial management with a minimum length of work of one year and a minimum of high school education as many as 82 people. The data source used in this study is primary data by giving questionnaires to respondents. The data analysis technique used is multiple linear regression analysis using the SPSS version 26 program. This research explains that organizational culture and apparatus competence have no effect on fraud prevention in village financial management. Meanwhile, morality and internal control systems affect fraud prevention in village financial management.Keywords: organizational culture, morality, apparatus competence, internal control system, fraud prevention in village financial management